Question: use de morgans law and the conditional logical equivalence p...
Use De Morgan’s Law, and the Conditional Logical Equivalence (p → r) ≡ (¬p ∨ r) to find the negation of the following expressions. You should have steps showing each application of De Morgan’s or the Conditional Equivalence, from the initial expression to the final form, which should have no negations outside of any logical connectives.
You can use other laws (the Commutative, Associative, and Double Negation Laws, in particular) without citing them, and you are not required to simplify any further once you have an expression that has no negations outside of any logical connective expressions.
(p ∨ r) → (s ∧ ¬p)
(p ∧ ¬r ∧ (s → r)) ∨ (¬r → p) ∨ s